Plasma Components which Interfere with Ristocetin-induced Platelet Aggregation - Baugh, Robert F; Brown, James E; Hougie, Cecil (Thrombosis and Haemostasis, 1975)
Normal human plasma contains a component or components which interfere with ristocetin-induced platelet aggregation. Preliminary examination suggests a protein (or proteins) which binds ristocetin and competes more effectively for ristocetin than do the proteins involved in ristocetin-induced platelet aggregation. The presence of this protein in normal human plasma also prevents ristocetin-induced precipitation of plasma proteins at levels of ristocetin necessary to produce platelet aggregation (0.5–2.0 mg/ml). Serum contains an apparent two-fold increase of this component when compared with plasma. Heating serum at 56° for one hour results in an additional 2 to 4 fold increase. The presence of a ristocetin-binding protein in normal human plasma requires that this protein be saturated with ristocetin before ristocetin-induced platelet aggregation will occur. Variations in the ristocetin-binding protein(s) will cause apparent discrepancies in ristocetin-induced platelet aggregation in normal human plasmas.